A GeoHealth Call to Action: Moving Beyond Identifying Environmental Injustices to Co‐Creating Solutions. (3rd November 2022) - Hoffman‐Hall, A.; Gorris, M. E.; Anenberg, S.; Bredder, A. E.; Dhaliwal, J. K.; Diaz, M. A.; Fortner, S. K.; McAdoo, B. G.; Reano, D.; Rehr, R. C.; Roop, H. A.; Zaitchik, B. F.
Abstract: As marginalized communities continue to bear disproportionate impacts from environmental hazards, we urgently call for researchers and institutions to elevate the principles of Environmental Justice. The American Geophysical Union (AGU) GeoHealth section supports members' engagement in health‐related community‐engaged and community‐led transdisciplinary research. We highlight intersectional research that provides examples and actions for both individuals and organizations on community science and trust building, removing barriers created by scientific agency priorities and career expectations, and opportunities in education and policy. Justice does not start or end at one meeting; this is ongoing work that is active, evolving, and an ethical responsibility of AGU's membership. Plain Language Summary: GeoHealth was recently defined as a new field of science that combines earth, environmental, and health sciences with a mission to answer scientific questions important to the health of humans and our planet. An incredibly important topic within GeoHealth is how racism affects environmental and human health. This topic is known as Environmental Justice: the right of all people and communities to have equal and fair protection by environmental laws and policies, regardless of race or color. However, many scientists feel underprepared to apply Environmental Justice to their own research due to a lack of training. Using GeoHealth projects from the American Geophysical Union Fall Meeting 2021 as examples, we highlight recent research that provides examples and clear suggested actions for both individuals and organizations on community science and trust building, changing funding methods for science, education, and policy in order to incorporate Environmental Justice across the all of the types of research we conduct. Key Points: We, members of American Geophysical Union GeoHealth, urgently call for researchers to incorporate and elevate the principles of Environmental Justice in their work We discuss justice‐oriented capacity‐building strategies like co‐creating research with communities, education, and restructuring funding mechanisms We provide individual‐ and organizational‐level guidance on converting science into action, dismantling barriers, and overcoming challenges